Development of the Pulmonary Vein and the Systemic Venous Sinus: An Interactive 3D Overview - van den Berg, Gert (Public Library of Science, 2011)
Knowledge of the normal formation of the heart is crucial for the understanding of cardiac pathologies and congenital malformations. The understanding of early cardiac development, however, is complicated because it is inseparably associated with other developmental processes such as embryonic folding, formation of the coelomic cavity, and vascular development. Because of this, it is necessary to integrate morphological and experimental analyses. Morphological insights, however, are limited by the difficulty in communication of complex 3D-processes. Most controversies, in consequence, result from differences in interpretation, rather than observation. An example of such a continuing debate is the development of the pulmonary vein and the systemic venous sinus, or “sinus venosus”. To facilitate understanding, we present a 3D study of the developing venous pole in the chicken embryo, showing our results in a novel interactive fashion, which permits the reader to form an independent opinion. We clarify how the pulmonary vein separates from a greater vascular plexus within the splanchnic mesoderm. The systemic venous sinus, in contrast, develops at the junction between the splanchnic and somatic mesoderm. We discuss our model with respect to normal formation of the heart, congenital cardiac malformations, and the phylogeny of the venous tributaries.